Tari Batu Bolah di Sanggar Seni Misstahto Kabupaten Kampar Provinsi Riau - Endah Dwi Larasati; Syefriani Syefriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research was carried out with the aim of finding out the Batu Bolah Dance works at the Miss Tahto Art Studio, Kampar Regency, Riau Province. The method used in this research is a descriptive method using qualitative data. The data collection techniques used are observation, interviews and documentation techniques. In this research, the author conducted direct interviews at the Miss Tahto art studio with 3 people involved, namely, Misselia Nofitri as choreographer, Riska Juliani as dancer, and Gilang Ramadhan as musician. Based on Soedarsono's theory, the Batu Bolah dance has several movements, namely, the opening movement, the movement to pick flowers, the movement to take the shawl, the movement to stab, the movement to propose to the protected princess, the movement side by side, the movement facing each other, the movement to play with the scarf, the commander's arrival, the movement to look for puti protected, movement of resistance, movement of citizen unrest, movement of anger, and split stone movement. The musical instruments used are calempong oguong, katepak, gong, flute, djembe, drum and accordion. The floor designs used are straight line and curved line floor designs. The dynamics in this dance are changing levels, changing tempo, and changing energy. The theme of this dance tells about the legend of the split stone. The costumes used by female dancers are plain red clothes with borkat decorations on the shoulders, yellow mixed with red editing using a bun, a yellow scarf wrapped around a green belt, earrings and necklace accessories. The costumes used by male dancers are red bolos shirts, yellow tanjaks, yellow songkets and green belts. The make-up for female dancers uses beautiful make-up. The make-up for male dancers uses character make-up as a king. The stage used is a proscenium stage. The property used is a shawl. The lighting used is white light.